Inverse heat transfer analysis to determine the temperature or phase change-dependent refractive index of semitransparent materials. Issue 4 (3rd April 2021) - Wei, Lin-Yang; Qi, Hong; Niu, Zhi-Tian; Wen, Shuang; Ren, Ya-Tao
Abstract : Inverse estimation of the temperature/phase change-dependent refractive index of semitransparent media is studied in present work. The direct models (including the coupled radiation-conduction heat transfer and coupled radiation-phase change heat transfer exposed to the laser irradiation) are solved by the finite volume method. The inverse model adopts stochastic particle swarm optimization (SPSO) algorithm to retrieve the refractive index from the radiative responses on boundaries. To improve the search ability of SPSO, the chaos theory is introduced to optimize its initial position of particles. The laser type and irradiation time are analysed to obtain the optimal combination settings. The sensitivity analysis is done to prove that the refractive index can be retrieved accurately from the radiative responses on both boundaries. All the retrieval results show that the inverse theme is accurate and effective to estimate temperature/phase change-dependent refractive index of semitransparent media.